Pre-participation health evaluation in adolescent athletes competing at Youth Olympic Games: proposal for a tailored protocol - Adami, P. E.; Squeo, M. R.; Quattrini, F. M.; Di Paolo, F. M.; Pisicchio, C.; Di Giacinto, B.; Lemme, E.; Maestrini, V.; Pelliccia, A. (British Journal of Sports Medicine, 2019)
Objective: To promote sports participation in young people, the International Olympic Committee (IOC) introduced the Youth Olympic Games (YOG) in 2007. In 2009, the IOC Consensus Statement was published, which highlighted the value of periodic health evaluation in elite athletes. The objective of this study was to assess the efficacy of a comprehensive protocol for illness and injury detection, tailored for adolescent athletes participating in Summer or Winter YOG.